2018
DOI: 10.1002/ldr.3150
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land degradation from mining activities on the sediment fluxes in two large rivers of French Guiana

Abstract: We analyzed two contrasting catchments located among the world's largest unspoiled tropical rainforests impacted by mining in the northeastern coastlands of South America. We used the following: (a) mining, agricultural, and urbanized areas to compare the land use evolution with suspended sediments and sediment yields; (b) field monthly river suspended sediments in the two catchments (2004–2015: n = 154); (c) MODIS remote sensing water color technique in the Maroni basin to complete (n = 387) and extend field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…For the years 2019 and 2013, another area of maximum turbidity, quite distinct from the classical ETM, is observed upstream (Figure 3a-Upstream turbidity). The presence of an upstream turbidity area in the Maroni River could be related to fluvial sediment influx as it occurs in the rainy season when runoff values are high [44]. It should be noted, however, that the presence of this river turbidity zone for 2019 goes with the availability of only rainy season scenes for this year (Table 1).…”
Section: Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the years 2019 and 2013, another area of maximum turbidity, quite distinct from the classical ETM, is observed upstream (Figure 3a-Upstream turbidity). The presence of an upstream turbidity area in the Maroni River could be related to fluvial sediment influx as it occurs in the rainy season when runoff values are high [44]. It should be noted, however, that the presence of this river turbidity zone for 2019 goes with the availability of only rainy season scenes for this year (Table 1).…”
Section: Extensionmentioning
confidence: 99%
“…The total suspended solid concentration in French Guiana rivers is low [42], and the Maroni has been identified as among the world's rivers with the lowest concentrations [43], no doubt a reflection of the highly crystalline basement rocks and still largely forested nature of the catchments. However, Gallay et al [44] identified a notable 239% increase in the Maroni River's SPM after 2009 due to an upsurge in anthropogenic activities, notably gold mining and deforestation.…”
Section: Maroni River and Estuarymentioning
confidence: 99%
“…This same fact was observed in May 2016, month in which the percentage of POC content in the TSS was high (13%), but only a small fraction represented the dry weight of phytoplankton (0.6%), suggesting that this “excess” of POC originated from terrestrial sources. As previously mentioned, the Maroni River has increased its sedimentary yield by approximately 400% in the last 15 years mainly due to gold mining activities in the basin (Gallay et al, submitted). Therefore, it is expected that during the intense soil erosion caused by mining activities, the richest organic detritus soil layers are removed and lixiviated towards the river mainstreams, increasing the percentage of allochthonous POC in sediments during intense rain events.…”
Section: Resultsmentioning
confidence: 99%
“…Although alluvial gold mining activities performed in the Maroni Basin (Dezécache et al, ; Rahm et al, ) have increased the sediment yield in the Maroni River (Gallay et al, submitted), both the Maroni and Oyapock Rivers showed low values of TSS, with weighted mean concentrations of 31.5 mg L −1 for the Maroni River and 8.2 mg L −1 for the Oyapock River. This is because the Guiana Shield has one of the lowest erosion rates in the world, with only two metres eroded every 1 million years in French Guiana and Suriname (Théveniaut & Delor, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation